Analisis Uji Fisik dan Kimia Daun Sirsak (Annona muricata L.) yang dikeringkan dengan Suhu Berbeda Menggunakan Mesin Tray Dryer - Qothrun Nada Sulistiani; Devi Tanggasari (Universitas Bumigora, 2024)
Soursop leaf drying is an important method to maintain the quality and shelf life of herbal raw ingredients, with different drying temperatures affecting the physical and chemical characteristics of soursop leaves. Drying can be done naturally and artificially. One of the artificial drying methods that can be used is the tray dryer method. Therefore, this study aims to analyze the effect of temperature on the tray dryer machine on the physical and chemical drying results of soursop leaves. The method used was an experimental method with a completely randomized design (CRD) model using one factor with three treatments. The results showed that different temperatures affected the weight loss of soursop leaf drying, and decreased the water content of soursop leaf drying. The best soursop leaf drying temperature to reduce weight loss and moisture content is using a temperature of 55 ℃. The soursop leaf drying process at 45 ℃ produced the best tannin content of 281.0 ppm and the best phytosterol of 17.42 mg. This research makes an important contribution in determining the optimal temperature on a tray dryer machine for drying soursop leaves that have the potential to be developed as a functional drink.